The silent struggle: The Psychosocial Impact of Unemployment on Youth - DIPELA, PERCY (Universitas Nahdlatul Ulama Surabaya, 2025)
Youth unemployment is a new worldwide crisis with lasting psychological and social impacts. Besides economic difficulties, youth unemployment leads to mental frustrations, low self-esteem, and social exclusion. Building on theoretical frameworks like Erikson's Psychosocial Development Theory and Jahoda's Latent Deprivation Model, this research explores the impacts of unemployment on emotional well-being and social integration. The article also analyzes the long-term impact of youth unemployment and how it affects employability and economic welfare in the future. The article also considers coping strategies, policy interventions, and social support systems' functions in reducing such effects. The termination of youth unemployment is crucial for economic growth and the generation of a psychologically stable and socially active generation. The data were collected and analyzed through the synthesis and exploration of extensive literature.